Conclusions - Brymer, Richard A. (Anthropologica, 2022)
Anthropological literature on small-scale societies, including some of the ethnographic material in this volume, suggests that the five organizational settings which form the conceptual setting for sociological theories of deviance are not universally present. Small scale societies are devoid of large, competing pressure groups with different values, differentiated regulatory organizations, distinct subcultures and a concept of the individual separate from the group. Consequently, many of the statuses and roles beloved of labelling theorists, e.g., moral entrepreneurs, generic labelling, deviant subcultures and deviant identities are absent. The development of a scalar model is the first step toward an understanding of deviance in cross-cultural terms. The emergence of deviant identity and deviant sub-cultures may perhaps be seen in some of the "middle-scale" ethnographic cases discussed in this volume, e.g., the self-confessed sorcery specialist. The scalar model assumes that large-scale societies are often composed of small-scale subunits, and both dominate and interact with small-scale folk societies which they partially absorb. A clash of values may occur. Thus spirit possession, which is not deviant in a small-scale unit, is viewed as deviant when that unit is absorbed within a larger group. Poaching and treasure-hunting, not necessarily regarded as deviant in small-scale rural groups, fall foul of the new industrial culture. The new scalar model will be of value not only to sociologists but also to anthropologists who have paid so little attention to deviance.